Avaliação da ação antifúngica de Citrus Limon Linn. frente a leveduras do Gênero Candida - Martins, Iolanda Maria Cariry Lacet de Barros (2009)
For a long time, the drugs used in the treatment and prevention of diseases and injuries were from plants becoming, often, the only resource that doctors had to treat their patients. In dentistry, the use of herbal medicines is still small and takes place mainly in the informal market. It is extremely important there be legislation to that end, in addition, research has been done in order to scientifically validate the use of some of these natural products as antimicrobial agents, which would open up space for clinical application in different diseases affecting the oral cavity especially those caused by Candida spp. In this context, this study aimed to evaluate the antifungal activity of essential oil of Citrus limon Linn. about 22 strains of Candida spp. by determining the CIM and CFM of the time evaluation of microbial death and morphological changes of the strains tested under the action of natural product tested. The CIM was obtained by the microdilution technique and CFM was obtained from the subculture of the concentration corresponding to the inhibitory and the two concentrations more concentrated. The evaluation of the interference of CIM product tested over time of microbial death was performed by counting viable cells. The study of morphological changes due to the action of the natural product was made from the microculture technique, with further observation under optical microscope. It was established the value of CIM of essential oil of C. limon between 0.078 and 0.156 mg/mL and CFM had a variation between 0.078 to 1.250 mg/mL. The kinetics of microbial death, there was fungicidal effect at concentrations of CIMx8 and CIMx4, with initial action after 2-4 hours of exposure of yeast. Microscopic observation of morphogenesis of the yeast under the action of the product tested showed inhibition in the formation of chlamydospores and pseudo-hyphae in most strains tested, this result was comparable to that of synthetic antimicrobial used as a control, the miconazole. We conclude therefore that the essential oil of C. limon has a important fungicide action and can be effective in the inhibition of Candida spp.